Hubungan Keragaman Konsumsi Pangan dan Social Engagement dengan Fungsi Kognitif Pra Lansia (Usia 45-59) Tahun di Kecamatan Driyorejo Gresik - Sabrina Destiasyavitrie Legawa; Salma Shafrina Aulia (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Cognitive decline is a common health issue experienced by pre-elderly individuals and can be influenced by dietary patterns and social engagement. This study aims to analyze the relationship between dietary diversity and social engagement with cognitive function in pre-elderly individuals aged 45–59 years in Driyorejo District, Gresik. A cross sectional design was used with a total sample of 70 pre-elderly participants selected through purposive sampling. Data were collected using the Individual Dietary Diversity Score (IDDS) questionnaire for dietary intake, the Index of Social Engagement (ISE) for social involvement, and the Mini Mental State Examination (MMSE) for cognitive function. The results showed that 54,3% of respondents had low dietary diversity, 38,6% had low levels of social engagement, and 35.7% experienced cognitive impairment. The study shows a significant relationship between the diversity of food consumption and social engagement with cognitive function (p <0.05). The more diverse food consumption and the better social involvement, the better the pre -elderly cognitive function.